Biology and Management of Tasselflower (Emilia spp.) in Ornamental Crop Production - Yuvraj Khamare; Chris Marble; Shawn Steed; Nathan Boyd (EDIS)
The name tasselflower refers to two similar and closely related species, red or lilac tasselflower and Florida tasselflower. These species are very common in Florida nurseries, greenhouses, and landscapes. This new 6-page article was developed to help nursery growers, landscape professionals, and the general public identify tasselflower species, understand their biology, and provide information on ways to manage this weed. Written by Yuvraj Khamare, Chris Marble, Shawn Steed, and Nathan Boyd.